Photoresponse of polyaniline-functionalized graphene quantum dots1. Issue 12 (28th March 2015) - Lai, Sin Ki; Luk, Chi Man; Tang, Libin; Teng, Kar Seng; Lau, Shu Ping
<x xml:space="preserve">Abstract</x> Optically tunable hysteresis and photoresponse in PANI-GQD composite.